Glory Style in Mandar Song Lyrics: A study of Mandar Tribe in South Sulawesi, Indonesia - Mutmainnah, Mutmainnah; Azis, Sulihin; Maulidya, Ulfa; Asrifan, Andi (JOURNAL OF ADVANCES IN LINGUISTICS, 2017)
This research background of how the style of language in the lyrics of Mandar song because of today many of the Mandar song lovers who lack understanding of the meaning that is in the lyrics Mandar song. The purpose of this research was to describe the fact of lyrics and identify the style of language in the lyrics of the song Mandar. This research applied descriptive qualitative research method. Descriptive research was a research procedure that produces descriptive data in the form of written words about the nature of individuals, circumstances, symptoms of certain groups that can be observed. The study, which began in September 2015 to January 2016, was unbound by space. In this study, it was found that the most commonly used hyperbola, asonation, and repetition style. Concluding remarks of the study were 174 lyric styles consisting of 8 personatic language styles, 6 metaphorical language styles, 7 simile / comparison language styles, 10 depersonative language styles, hyperbolic language styles, 7 parallelism languages, 4 style alliteration, 109 asonance and 17 repetition language styles.